2019
DOI: 10.1093/ejcts/ezz333
|View full text |Cite
|
Sign up to set email alerts
|

Positive family history of cardiovascular disease and long-term outcomes after coronary artery bypass grafting: a genetic paradox?

Abstract: OBJECTIVES Parental cardiovascular disease (CVD) is a known risk factor for premature CVD. It is unknown whether a positive family history (PFH) affects outcomes after coronary artery bypass grafting (CABG). METHODS Data come from a retrospective longitudinal study of CABG patients consecutively recruited from 2001 to 2018 (n = 5389). From this study, 2535 patients with premature CVD undergoing CABG under the age of 60 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…As an important finding positive family history was associated with lower mortality and MACE post-CABG which was in line with Preisler et al study [27]. As Ruttmann et al study suggests this may be because a positive family history as a reason for premature CVD is likely a more benign alternative regarding survival outcomes than some of the other causes that lead to this disease [28].…”
Section: Family Historysupporting
confidence: 72%
“…As an important finding positive family history was associated with lower mortality and MACE post-CABG which was in line with Preisler et al study [27]. As Ruttmann et al study suggests this may be because a positive family history as a reason for premature CVD is likely a more benign alternative regarding survival outcomes than some of the other causes that lead to this disease [28].…”
Section: Family Historysupporting
confidence: 72%
“…A positive (parental) family history of cardiovascular disease, especially at baseline, is a widely accepted risk factor for cardiovascular events in offspring [11,34]. Obesity is associated with the development of various lifestyle-related diseases and is also known to be a strong risk factor for CVD [14].…”
Section: Introductionmentioning
confidence: 99%
“…8 Numerous studies found that for patients with CVD in addition to risk factors, full consideration of positive family history of CVD is helpful for primary prevention and treatment decision-making in CVD. 9 Here, positive family history was also an important predictor.…”
Section: Discussionmentioning
confidence: 85%